(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
in this article, the methodology of memory development in the process of working on the passive and active vocabulary of children with underdeveloped speech, the state of mnestic processes in order to search for more effective ways and methods of correcting speech and non-speech functions in preschool children whose speech is not fully developed Directed learning is given.